Reconsidering the distinction between community and society and the possibility of unity in civil society - Çil, Dilek Arlı. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The aim of this thesis is to show that unity is possible in civil society. In the literature on the distinction between community and civil society, community is conceived as containing positive social relations which provide unity among the members, but society is conceived as containing negative relations which promotes isolation and alienation. I argue that this conception depends on Tönnies’ distinction between community and society. In Community and Civil Society, he characterizes community with acquaintanceship, sympathy and confidence; and society with strangeness, antipathy and mistrust. This distinction gives rise to the idea that by the emergence of society, community or what is valuable in community is lost. Heidegger adopts this idea, and he argues that we should revitalize what was there before, namely, communal relations. And this idea leads him to a nationalist course. Hegel, on the other hand, revises the distinction between community and society, and he conceives society as having both negative and positive characteristics. He argues that genuine unity can be developed in society through mutual recognition provided in the corporations. In this thesis, it is argued that Hegel’s conception of society and the theory of mutual recognition might be helpful in showing that unity can be developed within society, but his theory of the corporation is not adoptable today. The analysis of Hegel’s conception of society and the theory of recognition reveals the need for a new kind of community in philosophy and politics. For this reason, new social movements are considered in terms of their potential to function in place of Hegel’s corporations today.
Keywords: Civil society.